Correlation of signal-averaged electrocardiogram and late gadolinium enhancement cardiovascular magnetic resonance in the detection of myocardial fibrosis in arrhythmogenic right ventricular cardiomyopathy and other myocardial disorders - Mgidlana, Msimelelo Mzwamadoda (Department of Medicine, 2021)
Background. The diagnosis of fibrotic scar tissue in arrhythmogenic right ventricular cardiomyopathy (ARVC) and other cardiomyopathies is crucial as it forms the substrate for ventricular tachycardia (VT) and fibrillation (VT). Signal-averaged electrocardiography (SAECG) abnormalities are frequent in ARVC and in other cardiomyopathy-related ventricular arrhythmias. The correlation between cardiovascular magnetic resonance (CMR) late gadolinium enhancement (LGE) and parameters of SAECG in ARVC is not known. Method. Thirty-five patients [median age 32 years (IQR 25 – 46)] referred to the ARVC Registry at Groote Schuur Hospital were included in this retrospective study. SAECG was performed with high-amplification and filtered using bidirectional Butterworth filters between 40 and 250 Hz. A filtered averaged QRS (fQRS) was obtained and analysed for fQRS duration, low amplitude signal duration <40 mV (LAS40), and root-mean-square voltage in the last 40ms of the QRS (RMS40). LGE acquired at 5 to 20 minutes after intravenous administration of gadolinium (0.1mmol/kg to 0.2mmol/kg of body mass) was assessed. We evaluated the correlation between SAECG parameters and the presence of LGE. Results. Sixteen patients had definite ARVC, 5 had possible ARVC, 4 had idiopathic VT/VF, 2 had Athlete's heart, 1 had dilated cardiomyopathy (DCM), 1 had hypertrophic cardiomyopathy (HCM), 1 had SVT and 1 had pericardial constriction. LGE was present in 13 (81%) ARVC patients, 2 (40%) with possible ARVC, 1 (50%) with athlete's heart and in all patients with DCM and HCM. Patients with idiopathic VT/VF, pericardial constriction and supraventricular tachycardias had no myocardial LGE on CMR. Comparing patients with LGE and those without LGE on CMR, there were no differences in fQRS, (114ms [102.3 – 119] versus 111ms [99.5 -130], p = 0.608); LAS40 (34.5ms [16.8 - 40.8] versus 31ms [27.5 – 45], p = 0.566) and a RMS40 (23.5 µV [14.3 – 47.5] versus 33 µV [18.5 – 43.5], p= 0.621), respectively. LGE was present in 6 (60%) patients who had VT at presentation, in 9 (56%) with VT at baseline or follow-up and in all (2) patients who survived cardiac arrest. Three oneway analyses of variance (fQRS vs LGE, LAS40 vs LGE and RMS40 vs. LGE) confirmed that there was no correlation between LGE technique on CMR and SAECG for the detection of myocardial fibrosis in ARVC and other myocardial disorders: for fQRS F(1 , 33) = 1.47, p = 0.23,  2 = 0.02; for LAS40 F(1 , 33) =0.95, p = 0.34,  2 = 0.02 and for RMS40 F(1 , 33) = 0.36, p= 0.85,  2 = 0.02. Conclusion. In this study comparing assessment of myocardial fibrosis by LGE CMR and SAECG, there was no correlation between CMR and SAECG in detection of myocardial fibrosis in ARVC and other cardiovascular diseases.